Case report: Canadian consensus on chlormethine gel use in mycosis fungoides-CTCL: literature review and real-world experience - Litvinov, Ivan V.; Abu-Hilal, Mohannad; Alhusayen, Raed; Delisle, Bernard; Dutz, Jan; Guénin, Sophie; Ho, Vincent; Kirchhof, Mark G.; Pehr, Kevin; Roberge, David (Frontiers in Medicine, 2024)
Mycosis fungoides (MF) is the most common type of cutaneous T-cell lymphoma (CTCL), representing the majority of all lymphomas arising in the skin. The disease treatment focuses on managing symptoms and preventing disease evolution. To date, there is no gold standard for MF-CTCL treatment. Chlormethine, a DNA alkylating agent, is a long-known treatment for CTCL. The new chlormethine 0.02% gel (CL-gel) formulation provides proven efficacy and ease of application, improving patient compliance and outcome. The current consensus paper and real-world experience with CL-gel in the treatment of early-stage MF-CTCL may help meet the unmet need for treatments in Canada. A modified Delphi process comprised a virtual meeting and an online follow-up. A panel of 9 board-certified dermatologists with expertise in cutaneous lymphoma and 1 radiation oncologist discussed the systematic literature review results, drew from clinical experience and the opinion of the panel to adopt and agree on five consensus statements. The panel shared real-world patient cases to illustrate the use of chlormethine gel in a variety of patients across Canada. Five real-world patient cases were provided to illustrate the panels' use of chlormethine gel.